Staurophora ouniangaensis sp. nov. (Bacillariophyceae, Anomoeoneidaceae), a new diatom from the Ounianga Lakes in the Sahara, Chad - Rirongarti, Remadji; Cocquyt, Christine; Paillès, Christine; Sylvestre, Florence (Phytotaxa, 2022)
Modern diatom assemblages were investigated in the Ounianga Lakes located in the driest part of the Chadian Sahara. These lakes still exist today due to groundwater seepage. They contain a variety of diatom species, one of which could not be identified. Here we describe a new species of Staurophora, S. ouniangaensis sp. nov. based on detailed light and scanning electron microscopy observations. The new taxon presents all morphological characters attributed to this genus and differs from other Staurophora species mainly by its specific valve outline and the slightly twisted frustules along the transapical axis. We compared this new species with the morphologically resembling Cymbella obtusa which was reported from Chad. The latter taxon has a much coarser stria density than our newly described species. Staurophora ouniangaensis sp. nov. supports that Staurophora species prefer inland saline environments. Indeed, in the Ounianga lakes, the new species was mainly observed in mesosaline to hypersaline waters.